Cavernous sinus thrombosis: a case series analysis - Syntia Nusanti; Nadia Delima Andini; Lourisa Ruth Eldinia (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundAlthough uncommon, cavernous sinus thrombosis (CST) is a serious and potentially life-threatening condition that often presents with nonspecific signs and symptoms. Cavernous sinus thrombosis is associated with high morbidity and mortality, estimated at approximately 15% and 11% respectively. The complex diagnostic and treatment processes pose a challenge for healthcare providers, considering its elevated mortality and morbidity. We present four cases with varying clinical presentations and outcomes to provide valuable insights into the manifestations and management of CST. Case descriptionOur case series explored CST across age groups, including a case involving a pregnant woman. The clinical manifestations, laboratory data, imaging findings, pathogens, medications, surgical treatment, and clinical outcomes were analyzed. All cases were associated with one or more ophthalmic symptoms. All patients exhibited eye symptoms, with proptosis occurring unilaterally or bilaterally. Etiologies ranged from infections stemming from pimples and tooth cavities to an initially non-septic cause. Of the four cases presented, two proved fatal: one due to severe sepsis in a young man and the other initially aseptic but later progressing into sepsis in a geriatric man. The remaining two cases exhibited septic complications with complete recovery after prompt treatment. ConclusionSeverity and clinical courses of CST varied, emphasizing the need for careful consideration and tailored management strategies in CST cases. The prognosis of CST has improved with the advancement in treatment, but complications are not infrequent. Raising awareness regarding the potential for severe complications, such as cavernous sinus thrombosis, initiated by a common infection, is strongly encouraged.